CRIMINAL LAW AND CRIMINOLOGICAL ASPECT OF PROTECTION LIFE AND BODY IN THE REPUBLIC OF SERBIA AT THE LAST TWO DECADES (Heritage, 2022)
The criminal justice and criminological aspects of the study includes an analysis of the system of protection of life and physical integrity of the Republic of Serbia in the last two decades.The research of criminal law protection of life and body was conducted on the basis of legal-dogmatic, comparative and statistical methods, with a comprehensive analysis of the type and amount of sentences imposed on adult perpetrators of crimes against life and body in the last twenty years. The paper starts from two key hypotheses: the first - that today the number of punishable behaviors by which the protective object is human life and body is significantly higher than twenty years ago, and the second - that two decades ago crimes against life and body were more severe penalties compared to today. Although the punishments were stricter at the end of the 1990s (the death penalty was also prescribed), the RS Criminal Code prescribed a much smaller number of crimes against life and body compared to today. However, it should be concluded that a larger number of prescribed criminal offenses does not lead to more penalties nor to the imposition of heavier sentences. The study and comparison criminal and criminological sources has led to results - a significantly increased number of new incriminations of illegal behavior in the past two decades (murder with reckless violence, murder of a child or pregnant woman, murder of a family member he previously abused, female genital mutilation, etc.). The legislator is making a big step forward in 2019 when he introduces a life sentence in the RS Criminal Code, which has caused a lot of controversy. Statistical analysis of reports, charges and convictions for crimes against life and body indicates a rapid decline in the number of convictions in relation to the number of reports. In the segment of repressive measures, the death penalty was imposed in only one case in the period from 1998 to 2002, while the sentence of imprisonment for 40 years in the same period was imposed in only 62 cases. It should be noted that the short-term prison sentence of 3 (three) to 6 (six) months (a total of 2692 sentences in the observed period) was most often imposed. Mild penal policy and too many crimes against life and body lead to inefficiencies in the judiciary.
Keywords: crimes against life and body, criminal sanctions, criminological and criminal law aspect